Cultural and Educational Tourism in the Russian Federation: Basic Problems and Development Resources - Kabanova, Elena E.; Frolova, Elena V.; Medvedeva, Natalia V.; Vinichenko, Mikhail V.; Shimanskaya, Irina Y. (International Review of Management and Marketing, 2016)
The article is devoted to the urgent problem – the development of cultural and educational tourism. The empiric basis of the research is represented by data of the expert survey of the senior officers of local authorities of municipal formations of the Russian Federation, the results of the population survey, data of the Federal Service of State Statistics, the results of the researches of the All-Russian Center of Studying Social Opinion (ARCSSO), “Social Opinion” Fund, etc. The article distinguishes the most essential factors that prevent the development of the cultural and educational tourism in the Russian Federation, and defines basic recommendations on forming the resourceful provision of management practices related to developing the tourism attractiveness of territories. Under the modern conditions, a special attention is paid to the formation of the financial basis, scientific and informational provision of the management activity, support for local creative initiatives, popularizing of the internal tourism, and actualization of the local tourism potential. Keywords: tourism attractiveness of the territory, tourism potential, tourism, tourism tax, local initiatives, territory image. JEL Classifications: L83, R19